Get real: Orbitofrontal cortex mediates the ability to sense reality in early adolescents. Issue 4 (19th February 2020) - Liverani, Maria Chiara; Freitas, Lorena G. A.; Siffredi, Vanessa; Mikneviciute, Greta; Martuzzi, Roberto; Meskaldij, Djalel‐Eddine; Borradori Tolsa, Cristina; Ha‐Vinh Leuchter, Russia; Schnider, Armin; Van De Ville, Dimitri; Hüppi, Petra Susan
Abstract: Introduction: Orbitofrontal reality filtering (ORFi) is a memory mechanism that distinguishes whether a thought is relevant to present reality or not. In adults, it is mediated by the orbitofrontal cortex (OFC). This region is still not fully developed in preteenagers, but ORFi is already active from age 7. Here, we probe the neural correlates of ORFi in early adolescents, hypothesizing that OFC mediates the sense of reality in this population. Methods: Functional magnetic resonance images (fMRI) were acquired in 22 early adolescents during a task composed of two runs: run 1 measuring recognition capacity; run 2 measuring ORFi; each containing two types of images (conditions): distractors (D: images seen for the first time in the current run) and targets (T: images seen for the second time in the current run). Group region of interest (ROI) analysis was performed in a flexible factorial design with two factors (run and condition) using SPM12. Results: We found significant main effects for the experimental run and condition. The bilateral OFC activation was higher during ORFi than during the first run. Additionally, the OFC was more active while processing distractors than targets. Conclusion: These results confirm, for the first time, the role of OFC in reality filtering in early adolescents. Abstract : Orbitofrontal reality filtering (ORFi) is a memory mechanism that distinguishes whether a thought is relevant to present reality or not, and in adults it is mediated by the orbitofrontal cortex (OFC). In children, the OFC is one of the last regions to develop, but ORFi is already functional from age 7. Using functional magnetic resonance images, we probe for the first time the neural correlates of ORFi in early adolescents, hypothesizing that OFC mediates the sense of reality in this population.